PEGylated gold nanoprisms for photothermal therapy at low laser power density. Issue 99 (25th September 2015) - Ma, Xingqun; Cheng, Yuan; Huang, Yong; Tian, Ying; Wang, Shouju; Chen, Yingxia
Abstract : Small-sized PEGylated gold nanoprisms with ultrahigh photothermal conversion efficacy were achieved to induce photothermal therapy under a low power density laser. Abstract : This paper developed small-sized PEGylated gold nanoprisms (GNPs) to induce photothermal therapy at low laser power density. Upon irradiation of the laser at low power density (2 W cm −2 ), these PEGylated GNPs showed ultrahigh photothermal conversion efficacy ( η ≈ 70%) and produced enough heat to kill human breast cancer cells.